Parenting Styles and Student Resilience: The Role of Religiosity as a Mediator - Savira, Alice Whita; Suprawati, M.M. Nimas Eki; Ernest Justin (Universitas Ahmad Dahlan, 2024)
As one of the age groups vulnerable to depression, resilience is an essential aspect to consider among university students. Parenting styles are thought to play a role in the development of resilience; however, research findings on the relationship between these two variables remain inconsistent. In addition to parenting styles, religiosity has also been found to correlate with resilience. Religiosity is suspected to act as a mediator in the relationship between parenting styles and resilience. The role of religiosity as a mediator is important to examine, given that religiosity is a significant element in the lives of Indonesians. This study aims to investigate whether religiosity mediates the relationship between parenting styles and resilience. The instruments used in this study include the Parental Authority Questionnaire (PAQ) (α = 0.783 for the authoritarian parenting scale, α = 0.617 for the permissive parenting scale, and α = 0.830 for the authoritative parenting scale), the Centrality of Religiosity Scale (CRS) (α = 0.888), and the Connor-Davidson Resilience Scale (CD-RISC) (α = 0.920). A total of 412 university students in Indonesia participated in this study. Data analysis using GLM Mediation Analysis revealed that religiosity mediates the relationship between permissive parenting and resilience. Religiosity also mediates the relationship between authoritative parenting and resilience. A direct relationship between authoritative parenting and resilience was also identified. However, religiosity does not serve as a mediator in the relationship between authoritarian parenting and resilience. The implications of this study are discussed at the end of the article.